2014
DOI: 10.3389/fpsyg.2014.01484
|View full text |Cite
|
Sign up to set email alerts
|

Expertise among professional magicians: an interview study

Abstract: The purpose of the present investigation was to analyse interviews of highly regarded Finnish magicians. Social network analysis (N = 120) was used to identify Finland's most highly regarded magicians (N = 16). The selected participants' careers in professional magic and various aspects of their professional conduct were examined by relying on semi-structured interviews. The results revealed that cultivation of professional level competence in magic usually requires an extensive period of time compared with ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…The apprentices explained in interviews that they prefer to discuss professional issues with their local community of practice instead of strangers (in Germany, apprentices for two or three years parallely learn in schools and in VET companies). Rissanen et al (2010Rissanen et al ( , 2014 reported from the studies in magician's forum that developing expertise requires not only systematic effort in learning from personal and collective experiences and improving various aspects of performance but requires efforts in tapping into cultural resources in the field, guidance from mentors, sharing professional know-how, helping to solve others' problems and brainstorming for new practices, networking, testing, transforming practice, improving performance, self-reflecting and analyzing it. They found in magician's professional network that the relations between professional expertise, advice-asking and reputation (nomination as a respected expert, nomination as a backward supporter) were attributed only to very central persons in network, whereas collaboration and informal interaction were more evenly distributed among different members of the professional community.…”
Section: Patterns Of Epistemic Practices Used By Professionalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The apprentices explained in interviews that they prefer to discuss professional issues with their local community of practice instead of strangers (in Germany, apprentices for two or three years parallely learn in schools and in VET companies). Rissanen et al (2010Rissanen et al ( , 2014 reported from the studies in magician's forum that developing expertise requires not only systematic effort in learning from personal and collective experiences and improving various aspects of performance but requires efforts in tapping into cultural resources in the field, guidance from mentors, sharing professional know-how, helping to solve others' problems and brainstorming for new practices, networking, testing, transforming practice, improving performance, self-reflecting and analyzing it. They found in magician's professional network that the relations between professional expertise, advice-asking and reputation (nomination as a respected expert, nomination as a backward supporter) were attributed only to very central persons in network, whereas collaboration and informal interaction were more evenly distributed among different members of the professional community.…”
Section: Patterns Of Epistemic Practices Used By Professionalsmentioning
confidence: 99%
“…They found in magician's professional network that the relations between professional expertise, advice-asking and reputation (nomination as a respected expert, nomination as a backward supporter) were attributed only to very central persons in network, whereas collaboration and informal interaction were more evenly distributed among different members of the professional community. Rissanen et al (2014) found professional magicians of not extensively talking and being secretive of their experiences (magic tricks) although this is the only way magician knowledge can be learned. The access to learning happened in asking questions and getting advice and was provided only to those who had established trustladen relations with experts.…”
Section: Patterns Of Epistemic Practices Used By Professionalsmentioning
confidence: 99%
“…The necessarily secretive nature of magic implies that magicians were required to closely guard most of their knowledge about their own magic tricks. Although access to this secretive information used to be largely restricted to expert magicians (Rissanen et al, 2014), the digital culture in general and Internet, in particular, have changed the ease with which this information can be accessed. Before TV, videos and the Internet, learning magic relied on a fragile mentor relations and the support of senior experts who held strong gatekeeper positions.…”
Section: Digital Transformations In the Field Of Magicmentioning
confidence: 99%
“…Firstly, the social networking questionnaire was administered to 120/148 well-known Finnish magicians and other influential background people (response rate: 81%; age distribution: 17-86 years) (Rissanen et al, 2010). Secondly, on the basis of the social network data, we identified 16 professional magicians as subjects for semi-structured thematic interviews focused on the effects of digital technological transformations not addressed in our earlier published studies (Rissanen et al, 2013;Rissanen et al, 2014). Thirdly, we carried out supplementary interviews on 10 of the 16 previously interviewed individuals since the first round did not provide sufficiently detailed information.…”
Section: Participants and The Contextmentioning
confidence: 99%
See 1 more Smart Citation